Pelatihan Peserta pada PT Vinix Seven Aurum Yogyakarta - Ajrina Wina Maryam; Sri Harini (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Training is a strategic instrument in Human Resource Management (HRM) aimed at enhancing individual competencies, skills, and productivity in accordance with organizational needs. This study aims to analyze the implementation of training in the HR Management Division at PT Vinix Seven Aurum, Yogyakarta, based on indicators of participants, training objectives, training materials, and instructors. The study employed a qualitative descriptive method, collecting data through observation, interviews, pre-surveys, and documentation during the Field Work Lecture (Kuliah Kerja Lapangan/KKL) program. The results indicate several challenges in the training process, including low participant enthusiasm (64%), unclear training objectives (60%), training materials that are not fully comprehensible and relevant (42%), and uneven instructor competence and readiness (39%). Nevertheless, the company has implemented improvement efforts, such as developing structured training modules, enhancing participant engagement through discussions and assignments, and providing coordination and preparation for mentors. This study confirms that online training can significantly contribute to HR development if it is systematically designed, considers participant characteristics, and is supported by competent instructors. The findings are expected to serve as a basis for improving and developing the quality of digital training programs in the company.